EVALUASI METODOLOGIS TERHADAP KRITIK ARTHUR JEFFERY TENTANG SURAT AL-FATIHAH - Yoga Perdana Kusuma; Khairunnas Jamal; Mochammad Novendri (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2025)
This article critically examines Arthur Jeffery's view on the status of Surah al-Fatihah, as presented in his article "A Variant Text of the Fatiha." Jeffery argues that al-Fatihah is not an original part of the Qur'anic text, but rather a liturgical prayer inserted by compilers of the Mushaf after the prophetic era. This claim is based on three main premises: the difference between the linguistic style of al-Fatihah and the rhetorical style of the Qur'an in general, secondary reports on the Mushaf of Ibn Mas'ud that allegedly omit Surah al-Fatihah, and the existence of two variant readings of al-Fatihah in certain manuscripts. The research problem lies in the methodological validity of these three premises, especially when viewed against the standards of modern textual criticism and the epistemology of Islamic revelation. This research falls into the category of library research and is qualitative in nature, utilizing Arthur Jeffery's primary works as well as classical and modern Qur'anic scholarly literature. Data analysis was conducted using content analysis techniques to analyze Jeffery's arguments, hermeneutic assumptions, and philological framework. The results show that Jeffery's approach has several fundamental weaknesses. He is trapped in a hermeneutic bias because he assesses the structure of al-Fatihah through the paradigm of Christian liturgy rather than through Qur'anic rhetoric, which accommodates various forms of speech, including prayer. Claims regarding the Mushaf of Ibn Mas'ud are not supported by verifiable primary manuscript evidence. Furthermore, the two variants of al-Fatihah cited by Jeffery do not meet basic philological criteria and therefore cannot be considered valid textual witnesses. Therefore, Jeffery's conclusion that al-Fatihah is not authentic as an original part of the Qur'an cannot be methodologically justified.